Advancing Institutional Change to Encourage Faculty Participation in Research-Practice Partnerships. Issue 1 (January 2023) - Gamoran, Adam
University faculty have the talent, creativity, and training to tackle the serious challenges confronting our education system today, but the incentive structure in universities is often at odds with real-world contributions. What tensions are experienced by faculty who may be interested in partnership-oriented, engaged scholarship? How can these tensions be addressed? This chapter explores the tensions, particularly in the context of education research-practice partnerships, and provide examples from universities that are taking steps to lessen the tensions and encourage faculty participation in partnerships. By adopting new structures and incentives, these universities are providing a pathway to engaged scholarship that may ultimately increase the power of research to address the problems that educators face each day. However, university leaders who are implementing institutional change must grapple with long-established norms and traditions, and show how new ways of assessing the value of research will benefit universities as well as their communities.